The Effect of Christian Religious Education on Traditional Marriage Customs among the Tiv, Central Nigeria (Global Journal of Human-Social Science, 2015)
Marriage over the years has served as the institution of social value and a symbol of maturity in the society. This was the case up to the eve of the coming of Christianity and western education. The situation however, changed after Christianity and western education took firm roots on African soil, leading to the erosion of Tiv traditional marriage in contemporary times. The introduction of monogamy (western form of marriage) has infiltrated Tiv traditional system of marriage to the extent that it now finds expression through elements proper to Tiv culture, transforming or remaking it to bring about a "new creation." This paper sets out to examine the effect of Christian religious education on traditional marriage customs among the Tiv, North central Nigeria. The paper utilized qualitative approach which makes use of secondary sources and participant observation in collection and presentation of data. The paper observed that Tiv traditional marriage has experienced an infusion into Christianity due to the advent of western civilization in Nigeria. The paper recommends among others, that an infusion of Tiv traditional marriage into Christianity should be made to contextualize those practices that are not in line with the Christian oriented practices.
Keywords: traditional marriage; christian religious education and nigeria